Epidemiological aspects of Cryptosporidium spp. in calves of Tachira State in Venezuela - Moreno-Manresa, Carlos David (2018)
Diarrheic processes are most commonly involved in losses due to mortality or decline of growth and occur at early ages in the farm animals. In Venezuela, particularly in the Tachira state, the presence of protozoa of the genus Cryptosporidium has been determined in calves, but its relationship with a clinical gastrointestinal disease is not sufficiently evaluated. The objective of this work was to evaluate the epidemiology of Cryptosporidium spp. in the calves of herds in Tachira state and its relation with clinical manifestations of a digestive disease. 338 calves were randomly sampled during 2008. The epidemiological variables studied were: a) the age in months, taken from existing records in production units; b) the gender of the animal; c) the Tachira state zone (north or south); d) presence of obvious signs of diarrhea; and e) positivity or negativity to cryptosporidium upon coprological examination. 27% of the samples showed positivity to Cryptosporidium spp. by the Zielh Neelsen modified technique. The study suggests that this genus of protozoa constitutes an important risk factor for the presentation of diarrhea in calves from birth to weaning in the Tachira state (OR> 1, p <0.05); where 18.8% of cases of undifferentiated diarrhea may be related to the presence of the parasite (p <0.05). Infections were less common in older calves (OR <1; p <0.01); however, age did not act as a determinant factor for the presentation of diarrhea in already infected animals. Gender does not present as a risk factor for infection by Cryptosporidium spp.